Pyrroloindoline cyclization in tryptophan-containing cyclodipeptides mediated by an unprecedented indole C3 methyltransferase from Streptomyces sp. HPH0547. Issue 58 (1st July 2019) - Li, Hongxia; Qiu, Yan; Guo, Canxiong; Han, Meng; Zhou, Yuyang; Feng, Yue; Luo, Shizhong; Tong, Yigang; Zheng, Guojun; Zhu, Shaozhou
Abstract : The first indole C3 methyltransferase reported to catalyze pyrroloindoline cyclization in cyclic dipeptides, providing a feasible method to access diverse alkaloids. Abstract : Diverse bioactive alkaloids with a tryptophan 2, 5-diketopiperazine (DKP) core and an annulated structure forming a methylated pyrroloindoline–DKP assembly have been isolated from various microbial sources. However, little is known about their biosynthesis. In this study, a novel indole C3 methyltransferase from Streptomyces sp. HPH0547 was discovered and characterized. Structural elucidation of the products revealed that this enzyme catalyzed unique pyrroloindoline cyclization in tryptophan-containing cyclodipeptides. This is the first C3 methyltransferase reported to catalyze pyrroloindoline cyclization in cyclic dipeptides, which provides a feasible and simple method to access diverse alkaloids.